Learning during COVID-19 pandemic: A systematic literature review - Awal Kurnia Putra Nasution; Mustafa Kamal Nasution; Muhammad Hasyimsyah Batubara; Imam Munandar (International Journal of Evaluation and Research in Education (IJERE), 2022)
The COVID-19 pandemic has transformed education worldwide. Learning that is usually done offline has turned into online learning to avoid the spread of the COVID-19 virus. The purpose of writing this article is to describe the latest and updated learning conditions during the COVID-19 pandemic. What kind of learning was carried out during the COVID-19 pandemic, was the learning effective, how was the learning outcome, and the challenges faced. The systematic literature review is used to find answers to this article's purpose by synthesizing 53 articles selected according to the criteria. The synthesis results found that online learning was carried out using video conference as a substitute for face-to-face meetings, discussions, exams, and learning feedback using supporting applications. The internet was the direct support. Most of the learning shows significant results. Learning outcomes cannot be concluded whether it is good or not. There are many challenges during learning. It indicates that the world of education is not fully ready to transform from offline learning to online learning. A standard platform for online learning and rules of learning is required to minimize negative impacts and pay attention to the socio-emotional aspect.